Editorial: knowledge—a prescription for coeliac disease. Issue 4 (24th July 2018) - Swift, C.; Woodward, J. M.
Abstract : Linked Content This article is linked to Halmos et al paper. To view this article visithttps://doi.org/10.1111/apt.14791 .